Ethnography of Ulur-ulur Tulungagung Ritual and the Disconnected Memory - Ayuningtyas, Fitria; Hakim, Luqman (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2022)
This research aims to elucidate the reason behind the decline of villagers’ enthusiasm toward the Ulur-ulur ritual. Ulur-ulur ritual is a surviving agrarian ritual that was initially an integral part of and executed by four villages, including the Village of Sawo, Ngentrong, Gedangan, and Gamping Tulungagung Regency, as a manifestation of gratitude for the water of Buret Lake sustaining local’s agricultural activity. Historically, this ritual was dying in 1965, then revitalized in 1966 by the Paguyuban Sendang Tirto Mulyo. Currently, despite being set as the annual agenda of Tulungagung Tourism and officially acknowledged as an intangible cultural heritage by the Ministry of Education and Culture of Indonesia in 2020, the villagers' enthusiasm remains low. To uncover this phenomenon, this research employed an ethnographic approach. In-depth interviews and participatory research were executed to obtain data. The result showed that the ritual was constructed and operated by two memories: dhanyangan (ancestral spirit) and agricultural memories. However, the impact of the G-30-S tragedy escalated the tension in the society leading to the vandalism of the Sri-Sedono statues, which were the mnemonic device of agricultural memory. Meanwhile, the dhanyangan memory, constantly amplifying, created a clash with the more religious society’s narrative. The long vacuum period and the narrative shift make the association of ritual with the dhanyangan grow more robust, which contradicts the current social context. Furthermore, the revitalization, which was merely rooted in “defeated memory” led to the exclusion of the ritual from society.